Trace metals removal through a catalytic hybrid filter during cofiring of different biomass waste materials. (15th June 2015) - Contreras, M.L.; García-Frutos, F.J.; Ramos, R.; Sanz, D.; Bahillo, A.
Highlights: Trace elements (TEs) removal through a Catalytic Hybrid Filter System was evaluated. In the tests, olive tree pruning was cofired with refuse derived fuel and compost. TEs capture was strongly affected by size particle and the Ca content in ashes. Hg enrichment was enhanced with the unburned carbon content in fly ashes. Cd, Sb and Pb retention increased with sulphur concentration in ashes. Abstract: This paper aims at evaluating trace elements (TEs) removal during biomass cofiring in a fluidised bed pilot plant (1 MWth) equipped with a Catalytic Hybrid Filter System (CHFS), as air pollution control device, which combines electrostatic precipitation (ESP) and fabric filter (FF) in a unique approach to develop a compact but highly efficient system. One biomass (olive tree pruning (OP)) and two different waste materials (municipal refuse derived fuel (RDF) and compost (CO)) were employed in the cofiring tests, to evaluate the impact of the fuel in the process. TEs control through the CHFS as well as the effect of this system on mercury speciation, were evaluated. In addition, different factors which may be involved in TEs retention, such as ash matter composition and fly ash particle size, were investigated. Significant removal efficiency was achieved at the CHFS for most TEs studied, even for the most highly volatile TEs such as Hg and Se (40–60%), Cd (50–70%) and Sb (80–90%). Similar trends for TEs capture were observed for both fuel mixtures, obtaining the highest removal rates for Cu, Pb, Cr and Zn. However the retention of most TEs was significantly affected by the fuel employed, as consequence of the different composition and characteristics of ashes generated in each process. The capture of most TEs was seen to be highly influenced by the calcium content in fly ashes, while TEs of higher volatility were seen to be preferably retained in the finest size particles (<53 μm) from the catalytic FF module, despite of the fuel used, and this enrichment was enhanced with the unburned carbon content, in Hg case, and with sulphur and concentration, for Cd, Sb and Pb.